An Integration of Buddhadharma in Performing Duties of Thai Lawyers - Steannopkao, Preyanun; Yanavuddho, Boonsri; Ploychum, Suchao; Kanthik, Chamnong (Asian Interdisciplinary and Sustainability Review, 2019)
The objectives of this research are to study the roles and the professional duties of Thai lawyers, the Buddhadharma appropriate for such duties, the integration of Buddhadharma into the professional duties of Thai lawyers in order to solve problems related to their professions, and synthesize knowledge bases regarding the ways such integration takes place. The research methodology is mainly qualitative. It is found that the role and the professional duties of Thai lawyers is wide-ranging, covering both government and private sectors, with the most important duties being to assist people involved in litigation, to conduct cases in courts of law, and to undertake other duties along the judicial process. Based on reports of the Lawyers Council under the Royal Patronage, it is found that complaints against Thai lawyers are rooted in their failure to responsibly perform their duties as requested, their immorality, and their dishonesty while performing duties. The Buddhadharma suitable for solving these misconducts of Thai lawyers includes the virtues for a good household life, the five precepts and the five virtues, the good conducts, the four prejudices, and the moral shame and moral fear. An integration of Buddhadharma by Thai lawyers in performing their duties can be done by promoting truthfulness, humanitarianism, and righteousness so as to uphold justice and morality. The body of knowledge obtained from this study can be concluded in a model called “BSL Model” consisting of both the Buddhadharma principles and the legal principles. This would result in a standard for Thai lawyers, where lawyers shall perform duties according to both Buddhadharma and the rule of laws, so that problems with regards to the professional duties of Thai lawyers are sustainably resolved.